Ustadz Handy Bonny's Preaching Rhetoric on Social Media - Meli Wati (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study aims to analyze Ustadz Handy Bonny's preaching rhetoric on social media, which has become a popular platform for broadcasting religious teachings, especially among millennials who are the largest social media users. The method used is library research or content analysis, with a focus on examining the application of rhetoric to ensure effective and persuasive communication. The analytical framework in this study focuses on the preacher's use of diction, intonation, and expression. The results show that Ustadz Handy Bonny's rhetoric is very attractive to the public, especially young people, because of his relaxed and touching demeanor. He uses clear, fluent, and straightforward diction, and applies simple and slang language that is easy to understand. His intonation varies from low to high, adjusted to the material, accompanied by a firm voice emphasis to attract the listener's attention. In addition, he is expressive and enthusiastic, using body gestures and facial expressions that can create his own humor. The most frequently conveyed category of da'wah messages is about hijrah (migration), namely leaving behind all evil for a better state, which is relevant because he himself experienced dark times. In conclusion, the use of unique rhetorical elements appropriate to his da'wah target (youth) makes Ustadz Handy Bonny's communication on social media effective and persuasive.